Assessment of Planetary Protection Requirements for Spacecraft Missions to Icy Solar System Bodies - National Research Council (The National Academies Press, 2012)
NASA's exploration of planets and satellites during the past 50 years has led to the discovery of traces of water ice throughout the solar system and prospects for large liquid water reservoirs beneath the frozen ICE shells of multiple satellites of the giant planets of the outer solar system. During the coming decades, NASA and other space agencies will send flybys, orbiters, subsurface probes, and, possibly, landers to these distant worlds in order to explore their geologic and chemical context. Because of their potential to harbor alien life, NASA will select missions that target the most habitable outer solar system objects. This strategy poses formidable challenges for mission planners who must balance the opportunity for exploration with the risk of contamination by Earth's microbes, which could confuse the interpretation of data obtained from these objects. The 2000 NRC report Preventing the Forward Contamination of Europa provided a criterion that was adopted with prior recommendations from the Committee on Space Research of the International Council for Science. This current NRC report revisits and extends the findings and recommendations of the 2000 Europa report in light of recent advances in planetary and life sciences and, among other tasks, assesses the risk of contamination of icy bodies in the solar system.
Keywords: Space and Aeronautics

New Research Opportunities in the Earth Sciences - National Research Council (The National Academies Press, 2012)
The 2001 National Research Council (NRC) report Basic Research Opportunities in Earth Science (BROES) described how basic research in the Earth sciences serves five national imperatives: (1) discovery, use, and conservation of natural resources; (2) characterization and mitigation of natural hazards; (3) geotechnical support of commercial and infrastructure development; (4) stewardship of the environment; and (5) terrestrial surveillance for global security and national defense. This perspective is even more pressing today, and will persist into the future, with ever-growing emphasis. Today's world-with headlines dominated by issues involving fossil fuel and water resources, earthquake and tsunami disasters claiming hundreds of thousands of lives and causing hundreds of billions of dollars in damages, profound environmental changes associated with the evolving climate system, and nuclear weapons proliferation and testing-has many urgent societal issues that need to be informed by sound understanding of the Earth sciences. A national strategy to sustain basic research and training of expertise across the full spectrum of the Earth sciences is motivated by these national imperatives. New Research Opportunities in the Earth Sciences identifies new and emerging research opportunities in the Earth sciences over the next decade, including surface and deep Earth processes and interdisciplinary research with fields such as ocean and atmospheric sciences, biology, engineering, computer science, and social and behavioral sciences. The report also identifies key instrumentation and facilities needed to support these new and emerging research opportunities. The report describes opportunities for increased cooperation in these new and emerging areas between EAR and other government agency programs, industry, and international programs, and suggests new ways that EAR can help train the next generation of Earth scientists, support young investigators, and increase the participation of underrepresented groups in the field.
Keywords: Earth Sciences

Uranium Mining in Virginia: Scientific, Technical, Environmental, Human Health and Safety, and Regulatory Aspects of Uranium Mining and Processing in Virginia - National Research Council (The National Academies Press, 2012)
Uranium mining in the Commonwealth of Virginia has been prohibited since 1982 by a state moratorium, although approval for restricted uranium exploration in the state was granted in 2007. Uranium Mining in Virginia examines the scientific, technical, environmental, human health and safety, and regulatory aspects of uranium mining, milling, and processing as they relate to the Commonwealth of Virginia for the purpose of assisting the Commonwealth to determine whether uranium mining, milling, and processing can be undertaken in a manner that safeguards the environment, natural and historic resources, agricultural lands, and the health and well-being of its citizens.
Keywords: Environment and Environmental Studies

A Framework for K-12 Science Education: Practices, Crosscutting Concepts, and Core Ideas - National Research Council (The National Academies Press, 2012)
Science, engineering, and technology permeate nearly every facet of modern life and hold the key to solving many of humanity's most pressing current and future challenges. The United States' position in the global economy is declining, in part because U.S. workers lack fundamental knowledge in these fields. To address the critical issues of U.S. competitiveness and to better prepare the workforce, A Framework for K-12 Science Education proposes a new approach to K-12 science education that will capture students' interest and provide them with the necessary foundational knowledge in the field.
Keywords: Education

Understanding Water Reuse: Potential for Expanding the Nation's Water Supply Through Reuse of Municipal Wastewater - National Research Council (The National Academies Press, 2012)
In communities all around the world, water supplies are coming under increasing pressure as population growth, climate change, pollution, and changes in land use affect water quantity and quality. To address existing and anticipated water shortages, many communities are working to increase water conservation and are seeking alternative sources of water. Water reuse- the sue of treated wastewater, or "reclaimed" water, for beneficial purposes such as drinking, irrigation, or industrial uses- is one option that has helped some communities significantly expand their water supplies.
Keywords: Earth Sciences; Environment and Environmental Studies

Challenges and Opportunities in the Hydrologic Sciences - National Research Council (The National Academies Press, 2012)
New research opportunities to advance hydrologic sciences promise a better understanding of the role of water in the Earth system that could help improve human welfare and the health of the environment. Reaching this understanding will require both exploratory research to better understand how the natural environment functions, and problem-driven research, to meet needs such as flood protection, supply of drinking water, irrigation, and water pollution. Collaboration among hydrologists, engineers, and scientists in other disciplines will be central to meeting the interdisciplinary research challenges outline in this report. New technological capabilities in remote sensing, chemical analysis, computation, and hydrologic modeling will help scientists leverage new research opportunities.
Keywords: Earth Sciences; Environment and Environmental Studies

Improving Food Safety Through a One Health Approach: Workshop Summary - Institute of Medicine (The National Academies Press, 2012)
Globalization of the food supply has created conditions favorable for the emergence, reemergence, and spread of food-borne pathogens-compounding the challenge of anticipating, detecting, and effectively responding to food-borne threats to health. In the United States, food-borne agents affect 1 out of 6 individuals and cause approximately 48 million illnesses, 128,000 hospitalizations, and 3,000 deaths each year. This figure likely represents just the tip of the iceberg, because it fails to account for the broad array of food-borne illnesses or for their wide-ranging repercussions for consumers, government, and the food industry-both domestically and internationally. A One Health approach to food safety may hold the promise of harnessing and integrating the expertise and resources from across the spectrum of multiple health domains including the human and veterinary medical and plant pathology communities with those of the wildlife and aquatic health and ecology communities.
Keywords: Food and Nutrition; Health and Medicine

Macondo Well Deepwater Horizon Blowout: Lessons for Improving Offshore Drilling Safety - National Academy of Engineering; National Research Council (The National Academies Press, 2012)
The blowout of the Macondo well on April 20, 2010, led to enormous consequences for the individuals involved in the drilling operations, and for their families. Eleven workers on the Deepwater Horizon drilling rig lost their lives and 16 others were seriously injured. There were also enormous consequences for the companies involved in the drilling operations, to the Gulf of Mexico environment, and to the economy of the region and beyond. The flow continued for nearly 3 months before the well could be completely killed, during which time, nearly 5 million barrels of oil spilled into the gulf. Macondo Well-Deepwater Horizon Blowout examines the causes of the blowout and provides a series of recommendations, for both the oil and gas industry and government regulators, intended to reduce the likelihood and impact of any future losses of well control during offshore drilling. According to this report, companies involved in offshore drilling should take a "system safety" approach to anticipating and managing possible dangers at every level of operation—from ensuring the integrity of wells to designing blowout preventers that function under all foreseeable conditions—in order to reduce the risk of another accident as catastrophic as the Deepwater Horizon explosion and oil spill. In addition, an enhanced regulatory approach should combine strong industry safety goals with mandatory oversight at critical points during drilling operations. Macondo Well-Deepwater Horizon Blowout discusses ultimate responsibility and accountability for well integrity and safety of offshore equipment, formal system safety education and training of personnel engaged in offshore drilling, and guidelines that should be established so that well designs incorporate protection against the various credible risks associated with the drilling and abandonment process. This book will be of interest to professionals in the oil and gas industry, government decision makers, environmental advocacy groups, and others who seek an understanding of the processes involved in order to ensure safety in undertakings of this nature.
Keywords: Environment and Environmental Studies

Water Reuse: Potential for Expanding the Nation's Water Supply Through Reuse of Municipal Wastewater - National Research Council (The National Academies Press, 2012)
Expanding water reuse—the use of treated wastewater for beneficial purposes including irrigation, industrial uses, and drinking water augmentation—could significantly increase the nation's total available water resources. Water Reuse presents a portfolio of treatment options available to mitigate water quality issues in reclaimed water along with new analysis suggesting that the risk of exposure to certain microbial and chemical contaminants from drinking reclaimed water does not appear to be any higher than the risk experienced in at least some current drinking water treatment systems, and may be orders of magnitude lower. This report recommends adjustments to the federal regulatory framework that could enhance public health protection for both planned and unplanned (or de facto) reuse and increase public confidence in water reuse.
Keywords: Earth Sciences; Environment and Environmental Studies

Sea-Level Rise for the Coasts of California, Oregon, and Washington: Past, Present, and Future - National Research Council (The National Academies Press, 2012)
Tide gauges show that global sea level has risen about 7 inches during the 20th century, and recent satellite data show that the rate of sea-level rise is accelerating. As Earth warms, sea levels are rising mainly because ocean water expands as it warms; and water from melting glaciers and ice sheets is flowing into the ocean. Sea-level rise poses enormous risks to the valuable infrastructure, development, and wetlands that line much of the 1,600 mile shoreline of California, Oregon, and Washington. As those states seek to incorporate projections of sea-level rise into coastal planning, they asked the National Research Council to make independent projections of sea-level rise along their coasts for the years 2030, 2050, and 2100, taking into account regional factors that affect sea level.
Keywords: Environment and Environmental Studies; Earth Sciences

Sustainable Water and Environmental Management in the California Bay-Delta - National Research Council (The National Academies Press, 2012)
Extensively modified over the last century and a half, California's San Francisco Bay Delta Estuary remains biologically diverse and functions as a central element in California's water supply system. Uncertainties about the future, actions taken under the federal Endangered Species Act (ESA) and companion California statues, and lawsuits have led to conflict concerning the timing and amount of water that can be diverted from the Delta for agriculture, municipal, and industrial purposes and concerning how much water is needed to protect the Delta ecosystem and its component species. Sustainable Water and Environmental Management in the California Bay-Delta focuses on scientific questions, assumptions, and conclusions underlying water-management alternatives and reviews the initial public draft of the Bay Delta Conservation Plan in terms of adequacy of its use of science and adaptive management. In addition, this report identifies the factors that may be contributing to the decline of federally listed species, recommend future water-supple and delivery options that reflect proper consideration of climate change and compatibility with objectives of maintaining a sustainable Bay-Delta ecosystem, advises what degree of restoration of the Delta system is likely to be attainable, and provides metrics that can be used by resource managers to measure progress toward restoration goals.
Keywords: Environment and Environmental Studies; Earth Sciences

Evaluation of Bridge Scour Research - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2012)
TRB’s National Cooperative Highway Research Program (NCHRP) Research Results Digest 378: Evaluation of Bridge Scour Research summarizes key finding of three NCHRP projects that explored processes and predictions related to pier scour, abutment and contraction scour, and geomorphic scour.The results of the three research projects summarized in NCHRP RRD 378 were each published separately in the following documents:• NCHRP Web-Only Document 175: Evaluation of Bridge Scour Research: Pier Scour Processes and Predictions • NCHRP Web-Only Document 181: Evaluation of Bridge Scour Research: Abutment and Contraction Scour Processes and Prediction • NCHRP Web-Only Document 177: Evaluation of Bridge Scour Research: Geomorphic Processes and Predictions
Keywords: Transportation and Infrastructure

The Comprehensive Nuclear Test Ban Treaty: Technical Issues for the United States - National Research Council (The National Academies Press, 2012)
This report reviews and updates the 2002 National Research Council report, Technical Issues Related to the Comprehensive Nuclear Test Ban Treaty (CTBT). This report also assesses various topics, including:
Keywords: Conflict and Security Issues

Progress Toward Restoring the Everglades: The Fourth Biennial Review, 2012 - National Research Council (The National Academies Press, 2012)
Twelve years into the Comprehensive Everglades Restoration Project, little progress has been made in restoring the core of the remaining Everglades ecosystem; instead, most project construction so far has occurred along its periphery. To reverse ongoing ecosystem declines, it will be necessary to expedite restoration projects that target the central Everglades, and to improve both the quality and quantity of the water in the ecosystem. The new Central Everglades Planning Project offers an innovative approach to this challenge, although additional analyses are needed at the interface of water quality and water quantity to maximize restoration benefits within existing legal constraints. Progress Toward Restoring the Everglades: The Fourth Biennial Review, 2012 explains the innovative approach to expedite restoration progress and additional rigorous analyses at the interface of water quality and quantity will be essential to maximize restoration benefits.
Keywords: Environment and Environmental Studies; Earth Sciences

Himalayan Glaciers: Climate Change, Water Resources, and Water Security - National Research Council (The National Academies Press, 2012)
Scientific evidence shows that most glaciers in South Asia's Hindu Kush Himalayan region are retreating, but the consequences for the region's water supply are unclear, this report finds. The Hindu Kush Himalayan region is the location of several of Asia's great river systems, which provide water for drinking, irrigation, and other uses for about 1.5 billion people. Recent studies show that at lower elevations, glacial retreat is unlikely to cause significant changes in water availability over the next several decades, but other factors, including groundwater depletion and increasing human water use, could have a greater impact. Higher elevation areas could experience altered water flow in some river basins if current rates of glacial retreat continue, but shifts in the location, intensity, and variability of rain and snow due to climate change will likely have a greater impact on regional water supplies. Himalayan Glaciers: Climate Change, Water Resources, and Water Security makes recommendations and sets guidelines for the future of climate change and water security in the Himalayan Region. This report emphasizes that social changes, such as changing patterns of water use and water management decisions, are likely to have at least as much of an impact on water demand as environmental factors do on water supply. Water scarcity will likely affect the rural and urban poor most severely, as these groups have the least capacity to move to new locations as needed. It is predicted that the region will become increasingly urbanized as cities expand to absorb migrants in search of economic opportunities. As living standards and populations rise, water use will likely increase-for example, as more people have diets rich in meat, more water will be needed for agricultural use. The effects of future climate change could further exacerbate water stress. Himalayan Glaciers: Climate Change, Water Resources, and Water Security explains that changes in the availability of water resources could play an increasing role in political tensions, especially if existing water management institutions do not better account for the social, economic, and ecological complexities of the region. To effectively respond to the effects of climate change, water management systems will need to take into account the social, economic, and ecological complexities of the region. This means it will be important to expand research and monitoring programs to gather more detailed, consistent, and accurate data on demographics, water supply, demand, and scarcity.
Keywords: Environment and Environmental Studies; Earth Sciences; Conflict and Security Issues

Preparing for the Third Decade of the National Water-Quality Assessment Program - National Research Council (The National Academies Press, 2012)
The first two decades of the U.S. Geological Survey's National Water Quality Assessment (NAWQA) Program have provided a successful and useful assessment of U.S. water-quality conditions, how they have changed over time, and how natural features and human activities have affected those conditions. Now, planning is underway for the third decade (Cycle 3) of the Program outlined in the Science Plan, with challenges including ensuring that the NAWQA remain a national program in the face of declining resources, balancing new activities against long-term studies, and maintaining focus amidst numerous and competing stakeholder demands. The Science Plan for Cycle 3 articulates a forward-thinking vision for NAWQA science over the next decade, building on the previous cycles' data, experience, and products. Preparing for the Third Decade (Cycle 3) of the National Water-Quality Assessment (NAWQA) Program explains the national needs outlined in the plan, NAWQA's need to emphasize collaboration with other USGS and external programs, other federal agencies, state and local governments, and the private sector.
Keywords: Environment and Environmental Studies; Earth Sciences

Dam and Levee Safety and Community Resilience: A Vision for Future Practice - National Research Council (The National Academies Press, 2012)
Although advances in engineering can reduce the risk of dam and levee failure, some failures will still occur. Such events cause impacts on social and physical infrastructure that extend far beyond the flood zone. Broadening dam and levee safety programs to consider community- and regional-level priorities in decision making can help reduce the risk of, and increase community resilience to, potential dam and levee failures. Collaboration between dam and levee safety professionals at all levels, persons and property owners at direct risk, members of the wider economy, and the social and environmental networks in a community would allow all stakeholders to understand risks, shared needs, and opportunities, and make more informed decisions related to dam and levee infrastructure and community resilience. Dam and Levee Safety and Community Resilience: A Vision for Future Practice explains that fundamental shifts in safety culture will be necessary to integrate the concepts of resilience into dam and levee safety programs.
Keywords: Earth Sciences

Evaluation of the Updated Site-Specific Risk Assessment for the National Bio- and Agro-Defense Facility in Manhattan, Kansas - National Research Council (The National Academies Press, 2012)
Safeguarding U.S. agriculture from foreign animal diseases and protecting our food system require cutting-edge research and diagnostic capabilities. The Department of Homeland Security (DHS) and the U.S. Department of Agriculture (USDA) have embarked on an important mission to replace the aging Plum Island Animal Disease Center (PIADC) with a new facility, the National Bio- and Agro-Defense Facility (NBAF). When operational, this new facility would be the world's fourth biosafety level-4 laboratory capable of large animal research. It would serve as a critical world reference laboratory for identifying emerging and unknown disease threats, and would thus be a critical asset in securing the future health, wealth, and security of the nation.
Keywords: Biology and Life Sciences

Sustainable Development of Algal Biofuels in the United States - National Research Council (The National Academies Press, 2012)
Biofuels made from algae are gaining attention as a domestic source of renewable fuel. However, with current technologies, scaling up production of algal biofuels to meet even 5 percent of U.S. transportation fuel needs could create unsustainable demands for energy, water, and nutrient resources. Continued research and development could yield innovations to address these challenges, but determining if algal biofuel is a viable fuel alternative will involve comparing the environmental, economic and social impacts of algal biofuel production and use to those associated with petroleum-based fuels and other fuel sources. Sustainable Development of Algal Biofuels was produced at the request of the U.S. Department of Energy.
Keywords: Energy and Energy Conservation; Environment and Environmental Studies; Biology and Life Sciences

Approaches for Ecosystem Services Valuation for the Gulf of Mexico After the Deepwater Horizon Oil Spill: Interim Report - National Research Council (The National Academies Press, 2012)
On April 20, 2010, the Deepwater Horizon platform drilling the Macondo well in Mississippi Canyon Block 252 (DWH) exploded, killing 11 workers and injuring another 17. The DWH oil spill resulted in nearly 5 million barrels (approximately 200 million gallons) of crude oil spilling into the Gulf of Mexico (GoM). The full impacts of the spill on the GoM and the people who live and work there are unknown but expected to be considerable, and will be expressed over years to decades. In the short term, up to 80,000 square miles of the U.S. Exclusive Economic Zone (EEZ) were closed to fishing, resulting in loss of food, jobs and recreation. The DWH oil spill immediately triggered a process under the U.S. Oil Pollution Act of 1990 (OPA) to determine the extent and severity of the "injury" (defined as an observable or measurable adverse change in a natural resource or impairment of a natural resource service) to the public trust, known as the Natural Resources Damage Assessment (NRDA). The assessment, undertaken by the trustees (designated technical experts who act on behalf of the public and who are tasked with assessing the nature and extent of site-related contamination and impacts), requires: (1) quantifying the extent of damage; (2) developing, implementing, and monitoring restoration plans; and (3) seeking compensation for the costs of assessment and restoration from those deemed responsible for the injury. This interim report provides options for expanding the current effort to include the analysis of ecosystem services to help address the unprecedented scale of this spill in U.S. waters and the challenges it presents to those charged with undertaking the damage assessment.
Keywords: Earth Sciences